Total body bone mineral density and various spinal disorders: a Mendelian randomization study - Jiang, Qingyu; Gao, Haihao; Shi, Xudong; Wu, Yan; Ni, Wentao; Shang, Aijia (Frontiers in Endocrinology, 2023)
Introduction Observational studies have yielded inconsistent findings regarding the correlation between bone mineral density (BMD) and various spinal disorders. To explore the relationship between total-body BMD and various spinal disorders further, we conducted a Mendelian randomization analysis to assess this association. Methods Two-sample bidirectional Mendelian randomization (MR) analysis was employed to investigate the association between total-body BMD and various spinal disorders. The inverse-variance weighted (IVW) method was used as the primary effect estimate, and additional methods, including weighted median, MR-Egger, simple mode, and weighted mode, were used to assess the reliability of the results. To examine the robustness of the data further, we conducted a sensitivity analysis using alternative bone-density databases, validating the outcome data. Results MR revealed a significant positive association between total-body BMD and the prevalence of spondylosis and spinal stenosis. When total-body BMD was considered as the exposure factor, the analysis demonstrated an increased risk of spinal stenosis (IVW odds ratio [OR] 1.23; 95% confidence interval [CI], 1.14–1.32; P < 0.001) and spondylosis (IVW: OR 1.24; 95%CI, 1.16–1.33; P < 0.001). Similarly, when focusing solely on heel BMD as the exposure factor, we found a positive correlation with the development of both spinal stenosis (IVW OR 1.13, 95%CI, 1.05–1.21; P < 0.001) and spondylosis (IVW OR 1.10, 95%CI, 1.03–1.18; P = 0.0048). However, no significant associations were found between total-body BMD and other spinal disorders, including spinal instability, spondylolisthesis/spondylolysis, and scoliosis (P > 0.05). Conclusion This study verified an association of total-body BMD with spinal stenosis and with spondylosis. Our results imply that when an increasing trend in BMD is detected during patient examinations and if the patient complains of numbness and pain, the potential occurrence of conditions such as spondylosis or spinal stenosis should be investigated and treated appropriately.